Analisis Hambatan Siklus Sel Kanker Lidah Manusia SP-C1 yang Diinduksi oleh Biskoklaurin Alkaloid Cepharantine Menggunakan flow cytometry - SUPRIATNO - (Indonesian Journal of Cancer, 2010)
Flow cytometry has been widely used for detecting of apoptosis and cell cycle arrest on several human cancer cells. Supris clone-1 (SP-C1) cell is an oral tongue squamous cell carcinoma cell line which has rapidly growth, highly migration-invasion and metastatic to regional and distant lymph nodes. The aim of the study was to analyze the cell cycle arrest of SP-C1 inducted by cepharantine (CE) using flow cytometry. Treatment of SP-C1 cells with CE concentration 0, 5, 10 and 20 g/ml was carried out for 72 hours. The examination of cell cycle arrest of SP-C1 by flow cytometry revealed that CE with concentration 10 and 20 g/ml was significantly arrested of SP-C1 cell cycle in G1-S phase. Moreover, apoptosis was detected in G0 phase on the cells treated by CE 20 g/ml. These results concluded that CE had a potency to increase apoptosis with suppressing SP-C1 cell cycle phases.